Coming together or coming apart? Crises, uncertainty and tolerance - Niclas Berggren; Andreas Bergh; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2025)
Uncertainty affects people in various ways. It is frequently found to hinder investment and production in the economic sphere. In this study, we examine the empirical relationship between uncertainty and tolerance toward Muslims and Jews. Does uncertainty make people more or less tolerant? This question is particularly relevant given the prevalence of pandemics, wars, and financial crises. We investigate this relationship using the World Uncertainty Index, which measures the frequency of the word "uncertain" (and its variants) in The Economist Intelligence Unit country reports. By analyzing quarterly data from up to 56 countries between 1990 and 2020, we link country-level uncertainty to approximately 227,000 individual responses from the World Values Survey/European Values Study regarding whether respondents would like to have Jews or Muslims as neighbors. Leveraging the precise timing of survey interviews, we relate individual attitudes to prevailing uncertainty levels. Our results indicate a positive relationship between uncertainty and both tolerance indicators. Thus, for those concerned with attitudes toward minorities often subjected to prejudice, calm periods may pose greater risks to tolerance than volatile periods.
Keywords: F02; F22; Z13; Z18; 330; Tolerance; Uncertainty; Risk; Jews; Muslims; Crises